ANALISIS PENGARUH KUALITAS PELAYANAN, PRODUK, HARGA, DAN LOKASI TERHADAP KEPUASAN NASABAH (STUDI KASUS PADA PT BANK RAKYAT INDONESIA (PERSERO) Tbk. UNIT NGESREP SEMARANG) - Rizka Putri Rumastari; Aris Sunindyo (KEUNIS, 2019)
This study aims to determine and analyze the effects of service quality, product, price, and place towards the customers satisfaction (Case Study at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Ngesrep Semarang) both simultaneously or partially. The population in this study are all the customers at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Ngesrep Semarang. The data used in the research are primary and secondary data. The sample used of 100 respondents collected through the questionnaire by following the accidental sampling technique. Data analysis model using Multiple Linear Regression Analysis Model. Meanwhile, data analysis techniques use Statistical F Test, Coefficient of Determination Test (Adjusted R Square), and Statistical t Test. The result of the analysis and discussion show that the variables of service quality, product, price, and place simultaneously have a significant effects towards the customers satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Ngesrep Semarang. Partially, the variables of service quality, product, price, and place each have a positive and significant effect towards the customer satisfaction at PT Bank Rakyat Indonesia (Persero) Tbk. Unit Ngesrep Semarang.